Abnormal dot plots on current automated blood cell analyzer helped to yeast detection. Issue 4 (22nd February 2020) - Gérard, Delphine; Lesesve, Jean‐Francois
Abstract: Compromised data are usually flagged by instruments. This is the first report of yeast detection using the new launched Sysmex XN analyzer. Abstract : Compromised data are usually flagged by instruments. This is the first report of yeast detection using the new launched Sysmex XN analyzer.